DETERMINATION OF DISCLOSURE OF ISLAMIC SOCIAL REPORTS AT SHARIA BANK IN INDONESIA - Faiz, Ayatur Muhammad; Sukmaningrum, Puji Sucia (Jurnal Ekonomi dan Bisnis Airlangga, 2024)
Introduction: This study aims to determine the effect of profitability, bank size, bank age, debt to asset ratio, and syirkah funds to partially and simultaneously reveal Islamic Social Reporting on Islamic banks in Indonesia. Methods: This study uses a quantitative method with panel data regression analysis with EViews 12. The population used in this study is Islamic banks in Indonesia. Results: This study partially shows that profitability, Islamic bank size, and debt to asset ratio are not significant in Islamic Social Reporting disclosure. Meanwhile, the age of Islamic banks and temporary syirkah funds has a positive and significant effect on the disclosure of Islamic Social Reporting. Simultaneously, profitability, bank size, bank age, debt-to-asset ratio, and temporary syirkah funds have a significant positive effect on the disclosure of Islamic Social Reporting in Islamic banks in Indonesia in 2016-2021. Conclusion and suggestion: This study reveals that Islamic Social Reporting (ISR) disclosure in Indonesian Islamic banks is significantly influenced by bank age and temporary shariah funds, rather than profitability, size, or debt ratio. The findings highlight the importance of long-term commitment and stakeholder engagement in enhancing ISR practices, offering valuable insights for policymakers and stakeholders.